2012
DOI: 10.1111/cpsp.12007
|View full text |Cite
|
Sign up to set email alerts
|

Treating anger and aggression in military populations: Research updates and clinical implications.

Abstract: Anger is a common symptom among military populations with posttraumatic stress disorder (PTSD); yet, anger treatment has received relatively little attention in the literature. This discrepancy is surprising given that excessive anger is a key predictor of treatment outcome in PTSD. This study seeks to (a) build a case for the importance of a more explicit approach to understanding and treating anger in our military and veteran populations, (b) summarize the current literature base on treatment factors and tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 110 publications
0
48
0
Order By: Relevance
“…To more directly address this issue of causation and the feasibility of targeting aggression to reduce suicide risk, future research should assess the effects of anger treatment on suicide risk. A number of interventions have been developed to target anger and aggression in the military (e.g., Linkh & Sonnek, ; Shea, Lambert, & Reddy, ), but assessments of their effectiveness are limited (Morland, Love, Mackintosh, Greene, & Rosen, ), particularly as it relates to their impact on suicidality. In light of this, Morland et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To more directly address this issue of causation and the feasibility of targeting aggression to reduce suicide risk, future research should assess the effects of anger treatment on suicide risk. A number of interventions have been developed to target anger and aggression in the military (e.g., Linkh & Sonnek, ; Shea, Lambert, & Reddy, ), but assessments of their effectiveness are limited (Morland, Love, Mackintosh, Greene, & Rosen, ), particularly as it relates to their impact on suicidality. In light of this, Morland et al.…”
Section: Discussionmentioning
confidence: 99%
“…In light of this, Morland et al. () advocated for the development and evaluation of evidence‐based anger interventions that target service members’ anger holistically (e.g., family‐focused) and unobtrusively (e.g., technology‐based interventions).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ex‐combatants present with tendencies towards aggressive behaviour. These enhanced violent reactions are particularly associated with the hypervigilance symptom cluster of (combat‐related) PTSD (Jones, ; Klostermann, Mignone, Kelley, Musson, & Bohall, ; MacManus, Dean, & Jones, ; Morland, Love, Mackintosh, Greene, & Rosen, ). Subsequent to the experience of combat high (Grossman, , p. 243; Köbach, Schaal, & Elbert, ; Köbach et al ., in press), ex‐combatants did however also reported a shift towards perceiving self‐exerted violence as appealing (appetitive aggression; e.g., Elbert, Weierstall, & Schauer, ; Weierstall, Schaal, Schalinski, Dusingizemungu, & Elbert, ; Hecker, Hermenau, Maedl, Elbert, & Schauer, ; Weierstall et al ., ; Crombach & Elbert, ).…”
mentioning
confidence: 99%
“…For NET, Stenmark, Guzey, Elbert, and Holen () demonstrated that effects were smaller in ex‐combatants than in those who have never held a combatant status. Potential reasons for the reduced effect may include appetitive perceptions of violence (Elbert et al ., ; Köbach et al ., ), anger (Morland et al ., ; Forbes et al ., ; Forbes, Creamer, Hawthorne, Allen, & McHugh, ) and/or feelings of guilt (Kubany, ).…”
mentioning
confidence: 99%
“…1 PTSD is a common mental health disorder experienced by combat Veterans and is associated with high levels of depression, 2 substance abuse, 3 medical comorbidity, 4 mortality, 5 healthcare service use, 6,7 and impaired functioning. [8][9][10] Apart from the distress and reduced quality of life associated with this disorder, military Veterans with PTSD and their families are often confronted with job loss, 11 poor family functioning, 12 homelessness, 13 anger, violence, 14,15 and incarceration. 16 Approximately 11% of patients served by the Department of Veterans Affairs (VA) healthcare system have been diagnosed with PTSD.…”
mentioning
confidence: 99%